2021
DOI: 10.1007/s10943-021-01364-w
|View full text |Cite
|
Sign up to set email alerts
|

“A Divine Infection”: A Systematic Review on the Roles of Religious Communities During the Early Stage of COVID-19

Abstract: The objective of this systematic review was to summarize the roles that religious communities played during the early stage of COVID-19 pandemic. Seven databases were searched and a total of 58 articles in English published between February 2020 and July 2020 were included in evidence synthesis. The findings of the literature showed diverse influences of religion as a double-edged sword in the context of COVID-19 pandemic. Religious communities have played detrimental and/or beneficial roles as a response to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 84 publications
0
47
0
3
Order By: Relevance
“…Rababa et al ( 2021 ) found religious coping and spiritual well-being to be significant predictors of death anxiety in older adults. Lee et al ( 2021 ) reviewed 58 articles and summarized the roles religious groups have played during the COVID-19 pandemic. The review showed religious communities to have served as a critical resource for managing and controlling COVID-19 in many parts of the world.…”
Section: Spiritualitymentioning
confidence: 99%
“…Rababa et al ( 2021 ) found religious coping and spiritual well-being to be significant predictors of death anxiety in older adults. Lee et al ( 2021 ) reviewed 58 articles and summarized the roles religious groups have played during the COVID-19 pandemic. The review showed religious communities to have served as a critical resource for managing and controlling COVID-19 in many parts of the world.…”
Section: Spiritualitymentioning
confidence: 99%
“…In practical terms, religious organizations were considered as spaces for the diffusion of fake news about COVID-19 which further cultivated mistrust toward health professionals and health care initiatives among religious followers of these institutions (Agley, 2020 ). In addition, there were several cases where religious gatherings and practices were responsible for spreading the coronavirus since religious adherents failed to abide by social distancing recommendations (Lee et al, 2021 ). Our results also suggest that Tibetan Buddhists showed relatively low compliance with public health guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Research is only starting to document the varying roles of religion in global response to the COVID-19 pandemic (Quadri, 2020 ; Wildman et al, 2020 ). In a systematic review, Lee et al ( 2021 ) found that compared to atheists, religious people were less likely to abide by social distancing rules. For example, Agley ( 2020 ) demonstrated that religious commitment was negatively correlated with overall trust in science and scientists in a sample of 242 US-based Amazon Mechanical Turk users.…”
Section: Religious Responses To Covid-19mentioning
confidence: 99%
“…In this situation, they were looking for some support—‘believers’ could have found it in faith, and ‘non-believers’ in family members (with whom they were ‘lock-downed’). As shown in many previous studies religious beliefs can help to deal with psychological stress and trauma (during COVID-19, other pandemics and/or disasters) [ 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%